PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kantor Akuntan Publik di Wilayah Jakarta Selatan) - Agnes Christy Anggrainy; Andreas Andreas; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research examines the effect of competence, independence, and work experience on audit quality with an auditor ethics of moderating variable. The respondent in this research are auditors whom work in public accounting office in South Jakarta area. The amount of auditors that has been visited are 85 auditors. The method of sample determining is purpossive sampling method, meanwhile the method of data tabulation has been used by researcher is multiple regression and moderate regression analysis. The result show that competence, independence, and work experience effect significantly to audit quality. An auditor ethics can be a moderate variable for independence and work experience, but it can’t be a moderate variable for competence.Keywords: Competence, Independence, Work Experience, Auditor Ethics, Audit Quality